Benefits and approaches of incorporating land–sea interactions into coastal spatial planning: evidence from Xiamen, China - Wang, Shuo; Lin, Jiaju; Xue, Xiongzhi; Lin, Yanhong (Frontiers in Marine Science, 2024)
As the land–sea interface, the coastal zone has become an increasingly key life-support system. However, it is also highly threatened by exposure to both ocean- and land-based human activities. The interdependencies of the land and sea systems require the integration of land and sea spatial planning to achieve sustainable development of coastal zones. There are different forms of land–sea spatial management integration globally. Whether a form can positively impact and how different institutional settings affect outcomes need further explanation. Therefore, this study explores the reasons for China’s planning integration through institutional reform by using the Graph Model for Conflicts Resolution and establishes a quantitative contradiction assessment method to examine whether this top-down institutional approach has played a role at the urban level. The results show that the planning of Xiamen city after reform has a lower total contradiction value, grid cell average and cell maximum value. This progress is made possible by unifying the land–sea spatial planning departments. The equilibrium solution of the Graph Model for Conflicts Resolution indicates that due to the different preferences of the land–sea management departments and the central-local governments, it is challenging to implement the Land–sea Coordination policy under separate land–sea management. By integrating land–sea management departments, deep-seated sectoral interests between horizontal departments do not remain. The impacts on integrated management of divergences in preferences of different vertical governments can be reduced. The research results provide a universal method for the contradiction evaluation and a management reference for other regions that want to integrate land–sea coordination into urban spatial planning.